(The Effectiveness of Bamboo Charcoal as a Cigarette Smoke Filter) - Junaidi, Lukman; Wijaya, Hendra (Balai Besar Industri Agro, 2011)
Research on effectiveness effectiveness of using bamboo charcoal for cigarette smoke filter has been conducted .the aim of research was to investigate the characteristics of bamboo charcoal as a cigarette smoke filter .the results show the type of bambo charcoal andong and betung as well as particle size give no significance influence on benzene and chloroform adsorption ,while in contrarily give significance influence on significance influence on benzeneÂ and chloroform adsorption,while in contrarily give significance influence on 0idium adsorption .usingthe cigarette filter added with bamboo charcoal andong and betung could increase 90% tar adsorption in cigarette smoke compare to tar adsorption by cigarette filter without bamboo charcoal added .while bamboo charoal filter andong and betung could increase nicotine adsorption in cigarette smoke only 45% and 19% respectively compare to tar adsorption by cigarette filter without bamboo charcoal added. The size of mesh of bamboo charcoal filter andong and betung give same level of influence on tar and nicotine adsorption.the lower the size of mesh the higher the effectiveness on tar and nicotine adsorption.